Optical Methods in Experimental Mechanics. Part 9: The Diffraction Problem - Cloud, Gary (Experimental techniques (Westport, Conn.), 2003)
The first eight installments in this series have dealt with the nature of light and the first of the two cornerstones of optical methods of measurement, namely the interference of light waves. There is much more to be said about types and applications of interferometry, and, indeed, we will return to those subjects presently. It is time to augment our understanding of the behavior of light and to expand our arsenal of tools through study of the diffraction of light waves, the second of the two cornerstones. This segment provides some observations about our physical world that motivate study of the problem, mentions some potential applications, gives some background of the long history of the solution, and defines the problem in its simplest form.